Active vibration isolation system to improve free space optics communication - Abdul Muthalif, Asan Gani; Turahim, Khairiah K.; Ab Rahim, Syazwani (Springer, 2013)
A Free Space Optics (FSO) link consists of a transmitter and a receiver telescope which requires a continuous alignment for successful transmission of data. However due to certain factors, misalignment could occur between the transmitter and receiver telescope which later interrupts data transmission. One of the factors that contribute to this misalignment is unwanted vibration at the transmitter or receiver. This paper outlines the design and implementation of an active vibration isolation system prototype to tackle the problem of misalignment caused by vibration for an FSO communication. A prototype is fabricated and a control sys-tem is implemented with an objective to suppress vibration coming to the top plate where the transmitter or receiver will be placed. By applying an LQR controller to the system, a reduction of 25.8% of plate displacement and 49.2% of amplitude of frequency is achieved at excitation frequency of 12Hz.